An integrated marketing communications campaign for Mc Cafe - Co, Clarisse Joy O. (Animo Repository, 2012)
McCafé is a coffeehouse chain owned by McDonalds. The coffeehouse offers hot and cold beverages that cater not only to coffee drinkers, but to non-coffee drinkers as well. Based on the groups surveys and interviews, McCafé is a well-known brand but most people do not buy their products because they think that it is too expensive and they lack recommendations. Due to the presence of specialty coffeehouses like Starbucks, Coffee Bean & Tea Leaf, Figaro, and others, McCafé is not the consumers top of mind when it comes to coffee. Since McCafé is associated to McDonalds, the brand does not seem to have an identity of its own. The campaign aims to give an identity to McCafé. The campaigns objectives are: 1.) To change the consumer‟s perception of the brand, 2.) To reinforce the markets brand recall towards McCafé, and 3.) To heighten their awareness about the brand and encourage trial. This will be achieved through an interactive campaign that will be done digitally. The target market for the campaign are male and female college students, ages 16 to 21 belonging to socio-economic class AB and Upper C. These are college students that are technologically-driven and socially-active. This is why the campaign is aimed towards capturing the attention of this target group and involving them in the campaign through their ability to influence and their exposure to technology. Additionally, the market will be reached with the help of influential business and marketing school organizations.